Malaysian reminicence kit / Padma A. Rahman … [et al.] - A. Rahman, Padma; Dahlan, Akeshan; Sultan Ibrahim, Syamsul Anwar; Che Dom, Nazri; Ahmad Sharoni, Siti Khuzaimah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Malaysian reminiscence Kit (MRK) is a product that will assist occupational therapist when conducting reminiscence therapy with elderly patients. Reminiscence therapy is a therapy which uses photo, music or items from the past to improve mood, socialization and self-esteem among elderly. Occupational therapist often relies on western products when implementing therapy during their services. Content of the products from these countries often found to be inappropriate with Malaysian culture and norms. Consequently, therapist spend plenty of time to adapt the content in ensuring therapy purposes are met. This products is in a form of A3 (for better view) booklet which are divided infor five different themes: 1) entertainment 2) games 3) attire 4) buildings 5) daily items. Each theme comprised of different images from the past that are suitable for Malaysian multi-ethnic group's culture. Era of years of popularity will be also added to each image to guide your therapist. MRK will be able to assist local therapist in carrying out effective reminicence therapy as the content of the products are designed according to Malaysian culture and background.